International and national legal protection of the civilian population during an armed conflict: the example of Ukraine - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Стрельцов, Евгений Львович; Streltsov, Yevhen L.; Streltsov, Yevgen; Streltsova, Yevdokiia (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The protection of civilians is a basic ethical, strategic, and legal requirement for the international community and every democratic state, one of the key aspects of any military (combat) action. Such protection should not only be proclaimed, but also serve as a priority. If armed forces during armed conflicts rely on the foundation laid by international humanitarian law and adhere to civilised rules of military (combat) operations, then the damage caused to the civilian population can be minimised. This problem is also important in terms of the international and national legal protection of the civilian population during the international military conflict in Ukraine. © 2024 Lodz University Press. All rights reserved.
Międzynarodowe i krajowe aspekty prawne ochrony ludności cywilnej podczas konfliktu zbrojnego: przykład Ukrainy
Streltsova Ye. J. International and national legal protection of the civilian population during an armed conflict: the example of Ukraine / Ye. J. Streltsova, Ye. L. Streltsov // Acta Universitatis Lodziensis. Folia Iuridica. – 2024. – Vol. 106 : Russian Aggression Against Ukraine: The Fall and Rise of International Law. – P. 223–243.
Keywords: armed conflict in Ukraine; civilian population; criminal law; International Criminal Court; international humanitarian law; international law; war crimes